Science and scientification in South Asia and Europe - Michaels, Axel; Wulf, Christoph (Routledge, 2020)
Introduction to part I / Axel Michaels -- The art of grammar in context : 'science', human interest, and the construction of cultural and political worlds / Jan E.M. Houben -- Sanskrit and computer science / Anand Mishra -- Mathematics and Vedic mathematics / Axel Michaels -- The birth of the (exorcism) clinic : media, modernity, and the Jinn / William S. Sax -- The science question in alternative agricultures : zero budget natural farming and the emergence of agronomical pluralism in India / Daniel Münster -- Counting food? The pitfalls of caloric conception of nutrition and alternative theories of food / V. Sujatha -- Thinking about agriculture in an industrialising economy : an essay / Susan Visvanathan -- Introduction to part II: Philosophy, anthropology and history of the humanities / Christoph Wulf -- The dominance of scientific knowledge and the devaluation of other forms of knowledge / Christoph Wulf -- Modernity, colonialism and the "science of language" / Franson Manjali -- Scientism of early modern age and the prevailing scholastic discourse on principium individuationis / Babu Thaliath -- Prolegomenon to the study of science and religion. A philosophical and historical reflection / Dhruv Raina -- Technoscientific knowledge versus deep knowledge / Gabriele Sorgo -- Science cannot do it alone : habits, environment, and the enchantment of beauty / Mariagrazia Portera -- Knowledge and science in the art of living / Jörg Zirfas -- Transforming knowledge into cognitive basis of policies : a cosmopolitan from below approach / Vando Borghi -- The limits of science from the standpoint of philosophy / Jacques Poulain.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte; Wissenschaft; Europa; Südasien